"POLITICAL AND SOCIAL DISCOURSE IN SELECTED WORKS OF KENDRICK LAMAR - Sneha Thomas Varghese (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The genre of rap gained significant attention with regards to its close affinity with political and social themes. The impetus of hip- hop culture embeds a long lineage of political commentary and subversion that reflects the veins of oppressive dichotomy and the reassertion of power. The narrative of academic elitism that earlier debated the literary merit of analyzing hip- hop culture is gradually being replaced by the wave of new discursive and scholastic interventions within the genre of rap. The course of recent developments in the domain displays the revolutionary zeal of many artists who seeks to address pervasive issues that plague the contemporary socio-political scene. The present study aims to undertake a comprehensive analysis of the social and political elements of discourse in the works of Kendrick Lamar namely, Element and Humble. The research focuses on integrating Michel Foucault’s model of hegemonic discourse of power and knowledge, as well as the Du Boisian concept of double consciousness.